Membaca Alqurâ€™an sebagai Model Tafakkur dalam Upaya Menenangkan Jiwa di Masa Pandemi Covid 19: Studi Takhrij dan Syarah Hadis - Rafdi, Danendra Ahmad (Jurnal Riset Agama, 2021)
This study aims to discuss the hadith about reading the Qur'an as a model of meditation in an effort to calm the soul during the Covid-19 pandemic. This research is classified as a qualitative research type that uses literature study by applying the takhrij and syarah hadith methods. The analytical method used in this research is contemporary analysis. The results of the study indicate that the hadith about reading the Qur'an as a model of tafakkur is valid in terms of sanad and matan according to takhrij reviews. As for the syarah of the hadith, it shows that tafakkur through reading the holy verses of the Qur'an will apparently add a sense of mahabbah to Allah SWT. This love for Allah SWT will also be developed again by reflecting on the attributes and names of Allah SWT and accompanied by good deeds. This thing willÂ  increase the faith of a human being so it will give birth a peace in the soul. The conclusion of this study is that tafakkur by reading the Qur'an can also be a medium for spiritual healing for mental problems caused by the Covid-19 virus, although reading the Qur'an is not the only way to achieve peace of mind. Further research is needed on this matter, this research also recommends the collaboration of hadith experts, tafsor experts and also psychotherapy tasawwuf experts to explore studies on tafakkur by reading the Qur'an as an effort to calm the soul.